Current Scenario and Future Scope of Solar Energy in India (International Journal of Food and Nutritional Sciences, 2022)
In terms of the worldwide need for energy, the topic of Renewable Energy Sources (RESs) has been the most appealing subject for academics in recent decades, with numerous breakthroughs, technologies, and applications becoming reality. This paper discusses the overview of solar energy, scope of solar energy, Recent achievements of the MNRE India, Major Initiatives of the MNRE Indi and current energy policies in india. Solar energy is one of the most significant kinds of renewable energy sources that will aid India's long-term growth. Solar energy presently provides 5.1 percent of India's total energy needs, which is the second largest percentage of any renewable energy source. This studies will help in future study to understand the current scenario and future scope of solar energy in india.